ANALISIS BEBAN KERJA UNTUK MENENTUKAN JUMLAH KARYAWAN OPTIMAL PADA BAGIAN OPERASI SARANA PENYELENGGARAAN DIKLAT KILANG PPSDM MIGAS - Edi Hartono; Muh. Hisjam (Spektrum Industri, 2019)
PPSDM Migas is a company engaged in oil and gas. One factor that must be considered by the company is the distribution of workload to employees so that the effectiveness and efficiency of employees can be reached. The fact in the field, PPSDM Migas has just transferred its employees to PPSDM Jakarta, so there is a discrepancy between workload and number of employees. To overcome the problem of measuring workloads in PPSDM  Migas, this study uses a task per task approach.  This method will provide information about the allocation of employee human resources to complete the existing workload optimally. Based on the results of the workload measurement on PPSDM  Migas using the task per task approach it can be concluded that from the two positions as a pilot project there was one position which resulted in a mismatch between the workload and the number of office holders, namely 4 Tank employees and  Distribution  but  from  the calculation  results  it  takes  7  employees.  The position of Executor of Distillation Operations has the number of employees as many as 2 employees and from the results of the calculation required 2  employees, this shows the suitability between the number of employees and the workload on the position.  Based on the results of calculations from both positions, the position of Implementing Distillation Operations is included in the category of sufficient office efficiency. Whereas in the position of Implementing Tank and Distribution Installation get the medium category.